Mental and physiological mechanisms for athletic strength building and control - Trofimov, A. M. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to find factors of influence on the athletic strength building process and the relevant control mechanisms. The research methods applied included relevant psychological knowledge collection and systematization method; high nervous activity physiology and motor activity research methods; consciousness introspection method; and empirical data mining method.